Measuring grammatical development in bilingual Mandarin- English speaking children with a sentence repetition task - Woon, Chai Ping; Yap, Ngee Thai; Lim, Hui Woan; Wong, Bee Eng (Canadian Center of Science and Education, 2014)
Sentence repetition (SR) tasks have been used to measure children’s expressive language skills in normal and abnormal language development, and to examine the development of the speaking skills in second language acquisition, as well as to survey the proficiency of bilingual language development. Recently, SR tasks have been recognized as a potential psycholinguistic tool to identify bilingual children with language impairment. SR tasks are easy and quick to conduct, and a useful technique for obtaining quantitative and qualitative information about children’s lexical and morphosyntactic knowledge, as well as language development in a complex linguistic background. This paper reports the results of a pilot study conducted to investigate the performance of SR among bilingual Mandarin-English preschoolers, from age four to six. The task was conducted in both languages: Mandarin, and English, to examine the type of grammatical errors found among different age groups in the SR task. Studying the performance of SR in both languages could provide a better understanding of children’s language learning and their acquisition pattern in both the first and second language. Overall task accuracy in each language was compared; grammatical errors in the SR task were described qualitatively. The results showed that the linguistic characteristic of the stimulus materials in Mandarin and English influences the performance of these bilingual children in the SR task. The study also showed that the grammatical errors found in the SR tasks may have the potential of being used to distinguish children with typical and atypical language development in the first language (L1).